Rheology of natural gas hydrate slurry: Effect of hydrate agglomeration and deposition. (1st March 2019) - Ding, Lin; Shi, Bohui; Liu, Yang; Song, Shangfei; Wang, Wei; Wu, Haihao; Gong, Jing
Abstract: Hydrate formation and slurry flow experiments were conducted in w/o emulsion systems using a high-pressure flow loop to investigate the effect of hydrate agglomeration and deposition on hydrate slurry viscosity. Hydrate agglomeration process was recorded by a particle video measurement probe and the wetted agglomeration between hydrate particles and water drops was observed. Results showed that due to the effect of the water drops, it formed complicated hydrate agglomerates that could encapsulate water phase inside. Therefore, the unconverted water phase must be considered and a modified fractal dimension is required when estimating the hydrate effective volume fraction. The required fractal dimension for the agglomeration stage was larger than that for the stabilization stage by about 0.25. Hydrate deposition could affect the slurry viscosity by lowering the hydrate effective concentration and decreasing the flow diameter, while it had little effect on the required fractal dimension. Effect of water cut and shear rate were analysed. The slurry viscosity increased with the increase of the water cut and decreased with the increase of the shear rate, demonstrating the hydrate slurry was shear thinning. The best-fit fractal dimension was larger in higher water cut conditions and increased with the increasing shear rate. According to the experiment results, evolution of the head loss and slurry viscosity in a real long-distance transportation pipeline was divided into 5 stages.